2002
DOI: 10.1023/a:1020382011145
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Surface sediment samples from Strymonikos and Ierissos Gulfs were analyzed for Cu, Pb, Zn, Cr and Ni. The results showed that the sediment of Ierissos Gulf is more polluted with Cu, Pb, and Zn as compared to that of Strymonikos Gulf. The benthal area located off the load-out facility of the mining operations in the town of Stratoni, in Ierissos Gulf is established as the most polluted region. The distribution of Cr and Ni in both gulfs indicates the natural origin of these metals with the weathering of Strymon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 11 publications
1
7
1
Order By: Relevance
“…Other studies in samples of diverse fishing areas do not show such high levels of Cd, but they exceeded the levels established by the EU [11,25,48,57,58]. Concerning high Cd concentrations detected mostly in our NASSA specimens is mainly affected by the pollution of the cities in the North Aegean Sea coastline that became polluted due to marine, road and air traffic as well as due to domestic and industrial waste [30,32]. It may be concluded that T. alalunga may contain toxic metal Cd above the EU limits.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Other studies in samples of diverse fishing areas do not show such high levels of Cd, but they exceeded the levels established by the EU [11,25,48,57,58]. Concerning high Cd concentrations detected mostly in our NASSA specimens is mainly affected by the pollution of the cities in the North Aegean Sea coastline that became polluted due to marine, road and air traffic as well as due to domestic and industrial waste [30,32]. It may be concluded that T. alalunga may contain toxic metal Cd above the EU limits.…”
Section: Discussioncontrasting
confidence: 53%
“…Such high Hg levels found in the Mediterranean albacore may be attributed to the pollution from Hg mining wastewater in the sea [54]. Also, the above of 0.500 mg kg −1 wet wt Hg concentrations of the present study found mostly in the NASSA albacore samples, could be derived due to anthropogenic pressure along North Aegean coastline, in which exist coastal mining operations in Stratoni bay as well as several highly populated cities on the coastal zone (e.g., Thessaloniki, Kavala, Alexandroupolis), with widely industrialized and urbanized areas [28,29,30,31,32]. Furthermore, Evros, Nestos, Strymon, Axios, Loudias, and Aliakmonas river discharges, containing both natural and anthropogenic Hg, can contribute to increasing Hg contents of NASSA albacore.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Some common anthropogenic activities that contribute to the release of Cu, Pb, Zn, Cr, and Ni species into the coastal marine environment consist in the following: mining operations, effluent discharges from fertilizer factories, oil refineries, and municipal sewage, spills during shipping and terminal transfers, intense agricultural activities, leaks of oil from offshore platforms, and usage of anti-corrosive and anti-fouling paints. Furthermore, river discharges, containing both natural and anthropogenic Cu, Pb, Zn, Cr, and Ni species contribute to the increase in metal contents of the coastal environment [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been focused on sedimentology and geochemistry of sediments in the Aegean Sea (Ergin et al 1990;Yemenicioglu et al 1998;Karageorgis et al 1998;Batkı et al 1999;Kucuksezgin 2001;Sarı and Çagatay 2001;Stamatis et al 2002;Karageorgis et al 2005;Dalman et al 2006;Gavriil and Angelidis 2006;Kucuksezgin et al 2006). However, literature about its heavy metal concentrations from the eastern side of the Aegean Sea, along the Turkish coasts is scarce or limited.…”
Section: Introductionmentioning
confidence: 99%